Folic acid and melatonin mitigate diabetic nephropathy in rats via inhibition of oxidative stress - Ebaid, Hossam (Nutr Metab (Lond), 2020)
BACKGROUND: Diabetes mellitus is a global epidemic leads to multiple serious health complications, including nephropathy. Diabetic nephropathy is a serious kidney-related complication of type 1 or 2 diabetes that is prevalent in almost 40% of the people with diabetes. We examined whether folic acid and melatonin can reduce progression of nephropathy in rats of type 1 diabetes mellitus by controlling the level of oxidative stress, glucose, lipids, and cytokines. METHODS: Forty-two male albino rats were distributed into six groups, (n = 7 per group). Five of the groups were induced with diabetes by a single intraperitoneal injection of freshly prepared streptozotocin at a dose of 50 mg/kg body weight. After the induction of diabetes, the rats were treated with folic acid (100 mg/kg) and melatonin (10 mg/kg) separately and in combination daily for 6 weeks, whereas, the other diabetic group was treated with glibenclamide (5 mg/kg). One of the diabetic groups served as a positive control. One-way ANOVA was used to compare those five subfields ability followed by LSD multiple comparisons. RESULTS: The data indicated that diabetes significantly altered the body weight, lipids and kidney function. Diabetic rats exhibited a significant increase in plasma levels of urea, uric acid, creatinine, sodium, tumor necrosis factor alpha (TNF-α), interleukin-6(IL-6), cholesterol, triglycerides, and low-density lipoprotein (LDL). In contrast, plasma total protein, potassium, high-density lipoprotein (HDL) and interleukin-10 (IL-10) decreased significantly in diabetic rats compared to the control rats. Moreover, levels of renal malondialdehyde (MDA) and nitric oxide (NO) were significantly increased while the levels of renal glutathione(GSH), superoxide dismutase(SOD), and catalase (CAT) were significantly decreased in diabetic rats comparison to those in the control rats. Hence, diabetic rats treated with folic acid and melatonin alone as well as in combination showed improvements with respect to the indices in addition to a significant recovery observed via histopathology when compared to the diabetic group. CONCLUSIONS: These results revealed that treatment with folic acid in combination with melatonin in diabetic rats was more effective than treatment with either of folic acid or melatonin alone to alleviate the symptoms of diabetic nephropathy.